2022
DOI: 10.1182/blood.2021013839
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between anti-PF4 antibodies and anticoagulants in vaccine-induced thrombotic thrombocytopenia

Abstract: Life-threatening thrombotic events at unusual sites have been reported after vector-based vaccinations against severe acute respiratory syndrome coronavirus 2. This phenomenon is now termed vaccine-induced immune thrombotic thrombocytopenia (VITT). The pathophysiology of VITT is similar to that of heparin-induced thrombocytopenia (HIT) and is associated with platelet-activating antibodies (Abs) against platelet factor 4 (PF4). Therefore, current guidelines suggest nonheparin anticoagulants to treat VITT patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
3
19
0
1
Order By: Relevance
“…However, we observed the dilution effect also in sera obtained before IVIG treatment was started. Third, danaparoid in high concentrations can inhibit platelet activation in HIT 20 and VITT antibodies 21 . However, danaparoid treatment was excluded in the majority of patients assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed the dilution effect also in sera obtained before IVIG treatment was started. Third, danaparoid in high concentrations can inhibit platelet activation in HIT 20 and VITT antibodies 21 . However, danaparoid treatment was excluded in the majority of patients assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Third, danaparoid in high concentrations can inhibit platelet activation in HIT 20 and VITT antibodies. 21 However, danaparoid treatment was excluded in the majority of patients assessed. We suggest that the most likely explanation is based on the fundamental findings of Huynh et al, 22 who showed that VITT antibodies have very high avidity to PF4.…”
Section: Effect Of Antibody Dilution On the Pipamentioning
confidence: 99%
“…Dysregulated functions of platelets were involved in the vaccine-induced immune thrombotic thrombocytopenia (VITT) 44 . In platelets, rAdVV and RNA vaccination, FOS, JUN , and DUSP1 were commonly upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, differential gene expression analysis suggested that each vaccine type (rAdVV or mRNA) in individual cell cluster could have different immune response outcome, thus overall immune response should be different depending upon COVID-19 vaccination. Dysregulated functions of platelets were involved in the vaccine-induced immune thrombotic thrombocytopenia (VITT) 44 . In platelets, rAdVV and RNA vaccination, FOS, JUN, and DUSP1 were commonly upregulated.…”
Section: Altered Gene Expression and Signalling Pathways After Radvv ...mentioning
confidence: 99%
“…Finally, reconstituted WB samples were recalcified and run at a shear rate of 250s -1 (10 dyne) for 10 min as previously described. 25,32…”
Section: Methodsmentioning
confidence: 99%